PENINGKATAN AKTIVITAS DAN HASIL BELAJAR KOGNITIF SISWA MELALUI MODEL PEMBELAJARAN TIPE TRUE OR FALSE STAPADA PELAJARAN MATEMATIKA DI KELAS XI IPA4 SMAN I PASAMAN - Gusmanelli Gusmanelli (STKIP Pesisir Selatan, 2017)
Education is a shared responsibility between government, families and communities. Pendidikpun take a role in improving the quality of human resources Numerous attempts by the government to improve the quality of education, such as curriculum renewal. Nevertheless, we are still faced with the problem of low learning outcomes, resulting in low quality of education, Teachers as people directly involved in learning, can actually seek a lot of things to improve the quality of education, including using appropriate learning fun, and arouse the enthusiasm of students.This research is a type of class action (classroom action research), which is a re-investigation of the controlled cycle and reflective. This study was initiated in August 2012 to November 2012 research instrument is a quiz given each end of the lesson, test results of learning about the opportunities presented upon completion of the cycle, and the observation sheet student learning activities.The data were analyzed descriptively. The results showed that the activity of the students in doing the task, ask questions, express opinions, concluded the material, presenting duties, responding to questions, and answer the teacher's questions, is likely to increase from an average of the first cycle that 28.6% to 49.5% in the second cycle. From the analysis of learning outcomes obtained an average increase learning outcomes of the first cycle to the second cycle is 66.3 to 73.6 with classical completeness increased from 60.1% to 70.2%. It can be concluded that by using model-type kooperative True Or False Statement can be improved activity and student learning outcomes.